RAPID URBANIZATION: AN ADVERSE IMPACT ON THE GROUND WATER RESOURCES IN GURUGRAM (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2018)
Though, the development of tube well irrigation has contributed significantly to the increase in food production and reduction in poverty, sustainable development and management of this resource has posed many challenges in recent years. Major problems associated with the ground water development and management are over exploitation of ground water in several parts of the country, water logging and salinity due to rising water table in major irrigation commands, correct assessment of ground water potential and ground water pollution. Water is prime natural resource, a basic human need and precious natural asset. Water is also a vital part of socio-ecological system. This is evident from the fact that the ancient civilizations existed along the water courses and near water bodies.